The challenges of mathematics education for Indigenous teacher training - Gavarrete Villaverde, María Elena (2015)
In this article, I outline research carried out on in an Ethnomathematics course designed to train Indigenous teachers in Costa Rica, in which the following ethnic groups participated: Ngabes, Bribris, and Cabecares. The challenge is to develop a mathematical education that provides equitable conditions for the different groups within innovative curricular proposals. This research is based on the construct of ‘Cultural Mathematical Knowledge' which serves to describe intrinsic characteristics of socially differentiated groups and thus propose a model for teacher education. The design of the course incorporates an empirical base, a theoretical base, and a methodological base. It is a multicultural and multidisciplinary proposal based on Indigenous mathematics and on the ideas of mathematical enculturation, to be developed through curricular microprojects in Indigenous schools. The course promotes preparing the teacher as a researcher to shape him or herself mathematically, as someone who carries out appropriate educational actions in an academic environment in accordance with an ethnolinguistic reality, a cultural worldview, and awareness of the potential of the students of Indigenous schools.